Integrated pest management approach in pulse crops for sustainability of farmers income - SINGH, R P; SINGH, A K; SINGH, V P; SINGH, R K; DIXIT, DEEPSHIKHA (The Indian Journal of Agricultural Sciences, 2022)
In the present experiment a total of 213 and 60 demonstrations were conducted on pigeon pea and chickpea crops respectively during three consecutive years from 2017–18, 2018–19, 2019–20 for productivity enhancement and sustainability of farmers income. The findings in respect to pigeon pea and chickpea, overall yield trend of demonstrations ranged from 12.43–17.38 q/ha and 14.62–18.97 q/ha and yield increase ranged from 36.70–43.14% and 42.67–57.91% over the local practices yield, respectively. The average percent reduction in affected plant/m2 and percent reduction in affected pod/plant were recorded 45.92 and 40.42 in pigeon pea and 45.48 and 44.56 in chickpea, respectively. The overall disease reduction was recorded 43.74% in pulse crops. The yield parameter reflected significantly more over district, state and national level productivity in pigeon pea and chickpea crop. Wide yield gap of both pulse crops also indicated that farmers should adopt latest production technologies with high yielding varieties and integrated plant protection components will subsequently change this alarming trend of galloping yield gap. Average gross returns and net returns of demonstration in pigeon pea and chickpea crops were 39.49 and 56.21% and 53.99 and 91.83% higher than the farmers’ practices respectively. Average benefit cost ratio was found higher throughout the study in pigeon pea and chickpea i.e. 3.34 and 3.01 respectively. The productivity was better over existing practices under demonstrations. Hence, pulses production and protection technology have a broad scope for increasing the area and production of pulse crops.